Semiotica : Journal of the International Association for Semiotic Studies / Revue de l'Association Internationale de Sémiotique (De Gruyter Mouton, 1969)
The official journal of the International Association for Semiotic Studies, founded in 1969 as one of the first scholarly journals in the field, Semiotica features articles reporting results of research in all branches of semiotic studies, in-depth reviews of selected current literature in the field, and occasional guest editorials and reports. The journal also publishes occasional Special Issues devoted to topics of particular interest.